Indication of zoonyms in idiomatic phrases (Based on the Chinese and Kazakh phraseologisms) - Кенжебaевa A. A.; Бейсембaев Б. Ш. (Journal of Oriental Studies, 2018)
This article discusses the cultural semantics of phraseological units of Kazakh and Chinese languages. The study led to the conclusion that the value-semantic aspect of the mentality of the people is nothing but the totality of systematized knowledge and ideas of people about the environment and the world, which are considered through the prism of their social and emotional experience.